2008
DOI: 10.1021/ef8006239
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Molecular-Mass Distribution Determined by Two-Step Laser Mass Spectrometry

Abstract: Two-step laser mass spectrometry (L 2 MS) is explored as a technique to measure the molecular-mass distribution of asphaltenes. Unlike widely used laser desorption/ionization (LDI) mass spectrometry, in which a single laser pulse is used to desorb and ionize asphaltenes, L 2 MS involves two laser pulses and spatially and temporally separates the desorption and ionization events. This process allows L 2 MS to measure the asphaltene molecular-mass distribution free from artifacts resulting from aggregation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
199
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(217 citation statements)
references
References 53 publications
15
199
1
1
Order By: Relevance
“…The modified Yen model provides us with a framework/foundation for understanding the dispersion of asphaltenes in crude oil and has found application and success in oilfield case studies (Mullins 2010). Pomerantz et al (2009) confirmed the molar mass distributions of asphaltene monomers using two-step laser mass spectrometry. The results show that petroleum asphaltenes have many components under a mass envelope beginning at 200 g/mol, peaking at ~600 g/mol and extending to 1000-1500 g/mol.…”
Section: Characterization Of Asphaltenes and Determination Of Parametsupporting
confidence: 54%
“…The modified Yen model provides us with a framework/foundation for understanding the dispersion of asphaltenes in crude oil and has found application and success in oilfield case studies (Mullins 2010). Pomerantz et al (2009) confirmed the molar mass distributions of asphaltene monomers using two-step laser mass spectrometry. The results show that petroleum asphaltenes have many components under a mass envelope beginning at 200 g/mol, peaking at ~600 g/mol and extending to 1000-1500 g/mol.…”
Section: Characterization Of Asphaltenes and Determination Of Parametsupporting
confidence: 54%
“…The soft ionization of petroleum molecules provided by ESI has been corroborated by good agreement of molecular weights measured by ESI with those measured by other soft ionization techniques such as two-step laser mass spectrometry (Hortal et al, 2007;Hortal et al, 2006;Pomerantz et al, 2008;Pomerantz et al, 2009;Rodgers and Marshall, 2007). ESI FT-ICR MS is useful for the analysis of complex mixtures because each elemental composition (C c H h N n O o S s ) has a unique molecular mass.…”
Section: Esi Ft-icr Msmentioning
confidence: 72%
“…For instance Small-Angle X-ray and Neutron Scattering (SAXS and SANS) experiments were generally performed at concentrations close to 10 g.L -1 for asphaltenes dissolved in model solvents 17,18,[48][49][50][51] . It was not until 1999, using techniques such as fluorescence depolarization technique [52][53][54][55][56] , fluorescence correlation spectroscopy [57][58][59] and mass spectrometry 60,61 that reliable results, accounting for the molecular aggregation at higher concentrations, became available. These results have shown that typical mean molecular weights of asphaltenes were ∼750 g.mol -1 with a factor of 2 in the width of the molecular weight distribution.…”
Section: Structurementioning
confidence: 99%